Heterogeneously catalyzed domino synthesis of 3-indolylquinones involving direct oxidative C-C coupling of hydroquinones and indoles - Kamble, Sumit B.; Vyas, Praneet P.; Jayaram, Radha V.; Rode, Chandrashekhar V. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-5/acsomega.7b00201/20170523/images/medium/ao-2017-00201p_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">A domino synthesis of 3-indolylquinones was achieved successfully via direct oxidative C–C coupling of hydroquinones with indoles over Ag2O and Fe3O4/povidone–phosphotungstic acid (PVP–PWA) catalysts using H2O2 in tetrahydrofuran at room temperature. Ag2O catalyzed the in situ oxidation of hydroquinone and 3-indolylhydroquinone intermediates, whereas ferrite solid acid, Fe3O4/PVP–PWA, with a 1:4:1 ratio of Fe3O4, PVP, and PWA, catalyzed the activation of quinones. The efficiency of this catalytic domino approach was established by a broad scope of substrates involving a variety of hydroquinones and quinones to give high yields (81–97%) of 3-indolylquinones. Fe3O4/PVP–PWA was separated magnetically, whereas simple filtration could separate Ag2O, both of which could be recycled several times without losing their activities.
Keywords: Carbonyl compounds (organic); Electron microscopy; Fourier-transform spectroscopy; Redox reaction